Analisis Biaya Layanan Diabetes Melitus dengan Komplikasi dan Faktor Penentu Inefisiensi Penanganan Diabetes Melitus di Rawat Inap RSUD Banyuasin Tahun 2015 - Rahman, Fahrul (UI Scholars Hub, 2016)
Since JKN was offiacially administered in general hospital on January 1st, 2014, there has been changing in hospital administration payment from the restrospective system (free for services) to the prospective system (INA-CBG’s). It is planned in 2019 that all the people in Indonesia is registered in BPJS (Universal Heath Coverage) as one of the facilities for public healt services provided by Banyuasin general hospital (RSUD Banyuasin) which ains to provide qualified services, yet still considering effiencies due to the lach of the government subsidies. This study aimed to analyze the cost and identify determinant factor in handling Diabetes Melitus with complications, so that it can be a reference to handle the cost in taking care of patients with Diabetes Melitus. This study applied descriptif analysis which using primary data (observation and interview) and secondary data from Banyuasin general hospital (RSUD Banyuasin) in 2015 meanwhile. The cost analysis was appliyng Activity Based Costing (ABC) method. The ABC method was applied to allocated the cost by identifying the cost driver which was the major cause for cost for financing services for Diabetes Melitus with complication. The result of this study showed that medical component was the determinant factor of the inefficiencies for Diabetes Melitus with complication services. There are many efforts that can be done by the hospital to overcome the ineficiencies, for instance, making quidance for clinical practies, making revision for hospital formulation, and using e-cataloq medicine consistently.